An Analysis of Political and Institutional Power Dispersion: The Case of Turkey - Ibrahim Tutar; Aysit Tansel (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This study examines the effects of fragmented governments and fiscal authorities on budget deficits in Turkey along with political business cycle effects. For econometric analysis we will use annual data from the period of 1960-2009. This paper sheds light on various dispersion indices and their use in the field of political power and fiscal performance. The results show that the power dispersion indices of governments and fiscal institutions significantly explain the increases in the ratio of budget deficit to GNP. The paper draws attention to the unification and better coordination of fiscal authorities in Turkey. The analysis has important policy implications for Turkey and other developing countries from the viewpoint of fragmented political and administrative dispersion of power and poor budget performances.
Keywords: P16; H72; C22; C43; 330; Political Business Cycles; Fragmentation and Power Dispersion; Public Budget; Turkey; Statistical Indices; Politischer Konjunkturzyklus; Haushaltsdefizit; Macht; Finanzpolitik; Politische Entscheidung; Türkei